Disparities in Prevalence of Key Chronic Diseases by Gender and Race/Ethnicity among Antiretroviral-Treated HIV-Infected Adults in the Us. Issue 1 (January 2013) - Buchacz, Kate; Baker, Rose K; Palella, Frank J; Shaw, Lauren; Patel, Pragna; Lichtenstein, Kenneth A; Chmiel, Joan S; Vellozzi, Claudia; Debes, Rachel; Henry, Keith; Overton, E Turner; Bush, Timothy J; et al.
Background: Certain sociodemographic subgroups of HIV-infected patients may experience more chronic disease than others due to behavioural risk factors, advanced HIV disease or complications from extended use of combination antiretroviral therapy (cART), but recent comparative data are limited. Methods: We studied HIV-infected adult patients in care during 2006–2010 who had been prescribed ≥6 months of cART. We analysed the prevalence of selected key chronic conditions and polymorbidity (having 2 or more out of 10 key conditions) by gender and race/ethnicity. Results: Of the 3, 166 HIV-infected patients (median age 47 years, CD4 + T-cell count 496 cells/mm 3, duration of cART use 6.8 years), 21% were female, 57% were non-Hispanic White and over half were current or former tobacco smokers. The five most frequent conditions among women (median age 45 years) were dyslipidaemia (67.3%), hypertension (57.4%), obesity (31.7%), viral hepatitis B or C coinfection (29.0%) and low high-density lipoprotein cholesterol (HDLc; 27.3%). The five most frequent conditions in men (median age 47 years) were dyslipidaemia (81.2%), hypertension (54.4%), low HDLc (41.1%), elevated triglycerides (32.3%) and elevated non-HDLc (26.8%). In multivariable analyses, Hispanic patients had higher prevalence of obesity and diabetes than White patients; Black patients had higher prevalence of obesity and hypertension but lower rates of lipid abnormalities. Of all patients, 73.7% of women and 66.8% of men had polymorbidity, with no evidence of disparities by race/ethnicity. Conclusions: Among contemporary cART-treated HIV-infected adults, chronic conditions and polymorbidity were common, underscoring the importance of chronic disease prevention and management among ageing HIV-infected patients.